Model Bimbingan Pranikah Bagi Calon Pengantin Dibawah Usia 19 Tahun - Muiz, Hanhan Abdul; Fajar, Dadang Ahmad; Rojudin, Rojudin (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
The aim of this research is to determine the stages of modeling the concept of premarital guidance for prospective brides and grooms under the age of 19 years. The research method uses descriptive qualitative data collection techniques using observation, written interviews and unwritten interviews. Data sources were taken from the Cileunyi District KUA, Functional and Honorary Religious Counselors, a doctor and UPT-KB Officers. The research results show that there are two models used in premarital guidance, namely the classical guidance model which is combined with other guidance participants and the individual guidance model which seeks to carry out the guidance in the guidance participant's private place according to the guidance participant's wishes. This guidance pattern has different aspects of administrative prerequisites, namely the existence of a court decision regarding marriage dispensation and the content of curative guidance material.